Composite adsorbent, preparation method and application thereof, and method for removing fluorine ions in photovoltaic wastewater

By mixing citric acid with chitosan and adding the composite adsorbent prepared after adding aluminum chloride solution, the problem of existing adsorbents being disturbed by other anions when adsorbing fluoride ions is solved, the effect of efficiently removing fluoride ions in photovoltaic wastewater is achieved, and the preparation cost is reduced.

CN119869467AActive Publication Date: 2025-04-25HEFEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510304595.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-25
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

When adsorbing fluoride ions, existing adsorbents are susceptible to other anions in photovoltaic wastewater, resulting in poor treatment of fluoride ions, and complex preparation process and high cost.

Method used

Citric acid is mixed with chitosan, added aluminum chloride solution and acidified to form a composite adsorbent supported on chitosan with amorphous alumina, and a composite adsorbent with excellent adsorption properties is prepared through a specific synthesis process.

Benefits of technology

It has achieved efficient removal of fluorine ions in photovoltaic wastewater, with a fluorine removal rate of more than 90%, and a fluorine ion concentration in the treated wastewater is less than 1.5mg/L. It is suitable for treating high-salt fluorine-containing wastewater, and the preparation process is relatively simple and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869467A_ABST
    Figure CN119869467A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water treatment, in particular to a composite adsorbent, a preparation method and application thereof and a method for removing fluorine ions in photovoltaic wastewater. The preparation method of the composite adsorbent comprises the following steps: uniformly mixing citric acid and chitosan according to a weight ratio of 5: 4 to obtain a mixed solution A; uniformly mixing an aluminum chloride solution and the mixed solution A according to a volume ratio of 4: 5 to obtain a mixed solution B; dropwise adding an alkali liquor I into the mixed solution B until the pH value reaches 7.0-8.0 to obtain a suspension C; standing and aging the turbid liquid C, sequentially washing with water and alcohol, and centrifugally freezing and drying to obtain the composite adsorbent. The composite adsorbent with a large specific surface area and a reasonable aperture structure is successfully synthesized by loading aluminum oxide on chitosan and introducing citric acid as a chelating agent, and the composite adsorbent can effectively resist interference of inorganic anions such as Cl <->, SO4 < 2-> and NO3 <->, keeps a good fluorine removal effect and is suitable for treating high-salt fluorine-containing wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a composite adsorbent and a preparation method and application thereof, and a method for removing fluoride ions from photovoltaic wastewater. Background Art

[0002] It is extremely important to effectively treat fluorine-containing wastewater from the photovoltaic industry, reduce water pollution and ecological environment damage caused by the discharge of fluorine-containing wastewater, and reduce the adverse effects on animals, plants and humans.

[0003] Among them, the adsorption method has the advantages of simple operation, wide applicability, high efficiency, low cost, and stable operation, and has become one of the most advantageous methods for deep defluorination. Among them, alumina is the most widely used and most effective adsorption material. Alumina has a large specific surface area and surface hydroxyl sites, and can effectively adsorb fluoride ions through electrostatic adsorption. However, the existing activated alumina still has obvious disadvantages such as low adsorption capacity, short service life, and narrow pH application range.

[0004] After searching, the invention with application number CN202310514430.4 discloses a porous Al2O3-La2O3 composite material supported by a carbon fiber structure and its use, which is prepared and synthesized by combining gelation technology and calcination. However, the synthesis steps of the adsorbent material are complicated, and the introduction of rare earth metals leads to high preparation costs. The invention with application number CN202010231050.6 discloses a preparation method and application of Zr / La co-modified cross-linked chitosan. This technology introduces chitosan into a composite adsorbent, and then the rarity of Zr and La metals greatly limits the promotion and application of this technology. Through the above search, it can be seen that the adsorbent in the prior art not only has a complex preparation process and high preparation cost, but also the adsorption effect of the prepared adsorbent on fluoride ions is also interfered by other anions in photovoltaic wastewater, resulting in poor adsorption effect on fluoride ions. Summary of the invention

[0005] In order to solve the technical problem that the adsorbent prepared by the prior art is easily affected by other anions in photovoltaic wastewater when adsorbing fluoride ions, resulting in poor treatment effect on fluoride ions, the present invention provides a composite adsorbent and its preparation method and application, and a method for removing fluoride ions in photovoltaic wastewater.

[0006] The present invention is implemented by the following technical scheme: A method for preparing a composite adsorbent comprises the following steps: 1% to 5% citric acid and 2g / L to 10g / L chitosan are mixed uniformly at a weight ratio of 5:4 to obtain a mixed solution A. Aluminum chloride solution with a molar concentration of 1mol / L to 5mol / L is added to the mixed solution A, and mixed uniformly to obtain a mixed solution B; the volume ratio of the aluminum chloride solution to the mixed solution A is 4:5. Alkali solution is then added dropwise to the mixed solution B until the pH of the mixed solution B reaches 7.0-8.0 to obtain a suspension C. After the suspension C is allowed to stand for aging, it is sequentially washed with water and alcohol for multiple times, and finally centrifuged and freeze-dried to obtain a composite adsorbent.

[0007] As a further improvement of the present invention, the fluorine removal rate of the composite adsorbent in photovoltaic wastewater within the pH range of 3-7 is higher than 90%, and the fluorine ion concentration in the treated photovoltaic wastewater is lower than 1.5 mg / L.

[0008] As a further improvement of the present invention, the aluminum oxide fixed in the chitosan is amorphous aluminum oxide, and the loading amount of the amorphous aluminum oxide is 15%-35% in terms of aluminum element.

[0009] As a further improvement of the present invention, the alkali solution 1 includes one of NaOH, KOH, and NH3·H2O.

[0010] As a further improvement of the present invention, the molar concentration of the alkali solution 1 is 0.5 mol / L to 10 mol / L.

[0011] As a further improvement of the present invention, the deacetylation degree of chitosan is 60%-80%, and the molecular weight is 5×10 4 Da~5×10 5 Da.

[0012] As a further improvement of the present invention, the static aging time is 10h-20h, and the freeze-drying time is 12h-24h.

[0013] The present invention also includes a composite adsorbent, which is prepared by the preparation method of the composite adsorbent. After the composite adsorbent adsorbs fluoride ions in photovoltaic wastewater, it can be desorbed and regenerated by alkaline solution 2.

[0014] As a further improvement of the present invention, the alkali solution II includes one of NaOH and KOH; the molar concentration of the alkali solution II is 0.5 mol / L-10 mol / L.

[0015] As a further improvement of the present invention, the composite adsorbent has a porous structure with a pore volume of 0.2 cm 3 / g-0.8cm 3 / g, specific surface area is 100cm 2 / g-800cm 2 / g.

[0016] The present invention also includes an application of the composite adsorbent as described above, wherein the -NH2 group, -OH group, -CH2 group and -CO group in the composite adsorbent can resist Cl - 、SO4 2- and NO3 - The fluoride ions in photovoltaic wastewater can be removed by chemical adsorption to prevent interference and specifically bind to fluoride ions in photovoltaic wastewater.

[0017] The present invention also includes a method for removing fluoride ions from photovoltaic wastewater, which comprises the following steps: pouring the composite adsorbent prepared by the preparation method of the composite adsorbent described above into the photovoltaic wastewater to be treated, and stirring. While stirring, the concentration of fluoride ions in the photovoltaic wastewater is detected in real time by a fluoride ion detection instrument: if the fluoride ion detection instrument detects that the fluoride ion concentration in the photovoltaic wastewater is higher than 1.5 mg / L, continue to add the composite adsorbent to the photovoltaic wastewater to be treated until the fluoride ion detection instrument detects that the fluoride ion concentration in the photovoltaic wastewater to be treated is lower than 1.5 mg / L.

[0018] The technical solution provided by the present invention has the following beneficial effects:

[0019] (1) The preparation process of the composite adsorbent provided by the present invention is to introduce chitosan as a modifier into activated alumina for the first time, and prepare a composite adsorbent with excellent adsorption performance through a specific synthesis process. This innovation not only solves the problems of low adsorption capacity and narrow pH application range of traditional activated alumina, but also significantly improves the stability and service life of the prepared composite adsorbent. At the same time, by introducing citric acid as a chelating agent, a composite adsorbent with a large specific surface area and a reasonable pore structure was successfully synthesized, so that the prepared composite adsorbent can achieve deep fluoride removal and meet the increasingly stringent wastewater discharge standards. And the composite adsorbent can effectively resist Cl - 、SO4 2- and NO3 - It can eliminate the interference of inorganic anions such as fluorine and maintain good defluorination effect, and is suitable for treating high-salt fluoride-containing wastewater.

[0020] (2) The composite adsorbent of the present invention can effectively increase the exchangeable groups on the surface of the prepared composite adsorbent by loading amorphous alumina on chitosan, change the specific surface area, and improve the adsorption amount. At the same time, citric acid is used. Citric acid can not only acidify chitosan, making it easier for amorphous alumina to be loaded on chitosan, but also promote the formation of macroporous and mesoporous structures of amorphous alumina, thereby improving the adsorption effect of the prepared composite adsorbent.

[0021] (3) The composite adsorbent of the present invention is prepared and synthesized by acidification with citric acid followed by in-situ precipitation. It not only has high-efficiency fluorine removal performance, but also has good environmental adaptability and economy. It provides an effective fluorine removal adsorbent for the deep fluorine removal field and can achieve deep fluorine removal. After adsorption by the composite adsorbent of the present invention, the concentration of fluorine ions in photovoltaic wastewater is lower than 1.5 mg / L, meeting the wastewater discharge standard. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is an appearance diagram of the composite adsorbent prepared in Example 4 of the present invention.

[0023] Figure 2 These are electron microscope images of the composite adsorbent prepared in Example 4 of the present invention at different magnifications under a scanning electron microscope.

[0024] Figure 3 This is a picture obtained after analyzing the composite adsorbent prepared in Example 4 of the present invention in an EDS spectrometer.

[0025] Figure 4 This is a picture of the composite adsorbent prepared in Example 4 of the present invention taken under a transmission electron microscope.

[0026] Figure 5 This is the X-ray diffraction pattern of the composite adsorbent prepared in Example 4 of the present invention.

[0027] Figure 6 This is a graph of the FT-IR spectrum of the composite adsorbent prepared in Example 4 of the present invention before and after adsorbing fluoride ions in photovoltaic wastewater.

[0028] Figure 7 Schematic diagram of the defluorination efficiency of the composite adsorbent prepared in Example 4, Comparative Example 1 and Comparative Example 2 of the present invention for fluoride ions in photovoltaic wastewater.

[0029] Figure 8 Schematic diagram of the defluorination efficiency of fluoride ions in photovoltaic wastewater under different pH conditions of the composite adsorbent prepared in Example 4 of the present invention and Comparative Example 2.

[0030] Fig. 9 This is a schematic diagram of the defluorination efficiency of the composite adsorbent prepared in Example 4 of the present invention for fluoride ions in photovoltaic wastewater under the interference of different anions.

[0031] Fig.10 Schematic diagram of the defluorination efficiency of fluoride ions in photovoltaic wastewater by the composite adsorbent prepared in Examples 4, 5 and 6 of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Example 1

[0034] With the development of the photovoltaic industry, photovoltaic wastewater has also increased. Photovoltaic wastewater is a type of wastewater with high salt content and a lot of fluoride ions. Excessive fluoride ions in water bodies will not only endanger ecological safety, but also pose a threat to human health. In the prior art, fluoride ions in photovoltaic wastewater are generally removed by physical adsorption. This physical adsorption method generally makes the adsorbent carry a positive charge, and the fluoride ions in the photovoltaic wastewater are adsorbed by the positive charge. However, since the adsorption sites of the adsorbent are limited, and photovoltaic wastewater also contains a large amount of Cl - 、SO4 2- and NO3 - Therefore, when the existing adsorbents adsorb fluoride ions in photovoltaic wastewater by physical adsorption, Cl - 、SO4 2- and NO3 - These inorganic anions will also be adsorbed by the adsorbent, thereby occupying many adsorbent sites. As a result, existing adsorbents cannot effectively remove fluoride ions in photovoltaic wastewater.

[0035] In order to solve this problem, the present embodiment provides a method for preparing a composite adsorbent, which comprises the following steps: 1% to 5% citric acid by volume and 2g / L to 10g / L chitosan by mass concentration are mixed in a weight ratio of 5:4 to obtain a mixed solution A. Aluminum chloride solution with a molar concentration of 1mol / L to 5mol / L is added to the mixed solution A, and the volume ratio of the aluminum chloride solution to the mixed solution A is 4:5, and mixed to obtain a mixed solution B. Alkali solution is then added dropwise to the mixed solution B until the pH of the mixed solution B reaches 7.0-8.0 to obtain a suspension C. After the suspension C is allowed to stand for aging, it is washed with water and alcohol for multiple times in sequence, and finally centrifugally freeze-dried to obtain a composite adsorbent.

[0036] In the above preparation process, we introduced chitosan as a modifier into activated alumina for the first time, and prepared a composite adsorbent with excellent adsorption performance through a specific synthesis process. This innovation not only solves the problems of low adsorption capacity and narrow pH application range of traditional activated alumina, but also significantly improves the stability and service life of the prepared composite adsorbent. At the same time, by introducing citric acid as a chelating agent, a composite adsorbent with a large specific surface area and a reasonable pore size structure was successfully synthesized, so that the prepared composite adsorbent can achieve deep fluoride removal and meet the increasingly stringent wastewater discharge standards. And the composite adsorbent can effectively resist Cl - 、SO4 2- and NO3 - It can eliminate the interference of inorganic anions such as fluorine and maintain good defluorination effect, and is suitable for treating high-salt fluoride-containing wastewater.

[0037] The composite adsorbent prepared by the above method includes -NH2 group, -OH group, -CH2 group and -CO group, which can resist Cl in photovoltaic wastewater. - 、SO4 2- and NO3 - The invention can remove the interference of inorganic anions such as fluorine ions and can specifically bind to fluorine ions in photovoltaic wastewater. The composite adsorbent in this embodiment is combined with fluorine ions by forming chemical bonds. This chemical adsorption method has a fast reaction speed, and the compound formed by the adsorbent on the adsorption surface has high stability and selectivity. The physical adsorption speed is relatively slow, and the thermodynamic parameters of the adsorption process are also small, which makes the reverse reaction of physical adsorption easy to occur. Therefore, the adsorbent of this embodiment can specifically bind to fluorine ions in photovoltaic wastewater by chemical adsorption, thereby improving the adsorption effect of fluorine ions in photovoltaic wastewater.

[0038] The composite adsorbent prepared by the above method is made of natural high molecular polymer chitosan as a carrier, and the pores of chitosan are embedded with alumina. The pore volume of the composite adsorbent is 0.2cm 3 / g-0.8cm 3 / g, specific surface area is 100cm 2 / g-800cm 2 / g. The pore volume is the volume of the micropores in the adsorbent, usually expressed as the volume of the micropores of the adsorbent per unit weight of the adsorbent. The pore volume is the effective volume of the adsorbent, which is the value calculated using the saturated adsorption capacity, that is, the volume of the adsorbate that the adsorbent can accommodate. Therefore, for the adsorbent, the larger the pore volume, the better the adsorption effect. For specific surface area, the larger the specific surface area, the better the adsorption capacity. Therefore, by measuring the pore volume and specific surface area of ​​the composite adsorbent prepared by the preparation method of this embodiment, it can be proved that the composite catalyst prepared in this embodiment has good adsorption capacity.

[0039] In this embodiment, by loading amorphous alumina on chitosan, the exchangeable groups on the surface of the prepared composite adsorbent can be effectively increased, the specific surface area can be changed, and the adsorption amount can be increased. At the same time, citric acid can not only acidify chitosan, making it easier for amorphous alumina to be loaded on chitosan, but also promote the formation of macroporous and mesoporous structures of amorphous alumina, thereby improving the adsorption effect of the prepared composite adsorbent.

[0040] The alumina fixed in the chitosan pores may be amorphous alumina, and the loading amount of the amorphous alumina may be 15%-35% in terms of aluminum element. Amorphous alumina has a high specific surface area and a controllable pore structure, which can improve the catalytic and adsorption capacity of the composite adsorbent.

[0041] Among them, the deacetylated fluorine content of chitosan is 60%-80%, and the molecular weight is 5×10 4 Da~5×10 5 Da. The standing aging time can be 10-20 hours, and the freeze drying time can be 12 hours to 24 hours. Freeze drying helps the prepared composite adsorbent to form a porous structure, thereby improving the adsorption effect of the prepared composite adsorbent.

[0042] The alkali solution 1 can be one of NaOH, KOH, and NH3·H2O. The molar concentration of the alkali solution 1 can be 0.5 mol / L to 10 mol / L. By adding the alkali solution 1, the amorphous aluminum oxide we need can be obtained, and the amorphous aluminum oxide can be loaded on chitosan, thereby achieving the preparation of the desired composite adsorbent.

[0043] The composite adsorbent prepared by the above preparation method is a spherical material, which can be desorbed and regenerated by alkali solution 2. This allows the composite adsorbent prepared by this embodiment to be recycled and reused, thereby improving its practicality. Alkali solution 2 can be one of NaOH and KOH. The molar concentration of alkali solution 2 can be 0.5 mol / L-10 mol / L.

[0044] Example 2

[0045] An application of a composite adsorbent, the composite adsorbent is obtained by the preparation method of Example 1. The -NH2 group, -OH group, -CH2 group, and -CO group in the prepared composite adsorbent can resist Cl - 、SO4 2- and NO3 - The fluoride ions in photovoltaic wastewater can be removed by chemical adsorption to prevent interference and specifically bind to fluoride ions in photovoltaic wastewater.

[0046] Example 3

[0047] A method for removing fluoride ions from photovoltaic wastewater, comprising the following steps: (1) pouring the composite adsorbent prepared by the preparation method of Example 1 into the photovoltaic wastewater to be treated and stirring. (2) using a fluoride ion detection instrument to detect the concentration of fluoride ions in the photovoltaic wastewater in real time while stirring. If the fluoride ion detection instrument detects that the fluoride ion concentration in the photovoltaic wastewater is higher than 1.5 mg / L, continue to add the composite adsorbent to the photovoltaic wastewater to be treated until the fluoride ion detection instrument detects that the fluoride ion concentration in the photovoltaic wastewater to be treated is lower than 1.5 mg / L.

[0048] Among them, in this embodiment, the fluoride ion detection instrument can be a fluoride ion analyzer.

[0049] Several specific preparation processes of the composite adsorbent are listed below. Please refer to Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 for details.

[0050] Example 4

[0051] A method for preparing a composite adsorbent comprises the following steps:

[0052] (1) Chitosan powder with a mass concentration of 5 g / L and a weight of 5 g was added to a citric acid solution with a volume fraction of 2% and a volume of 125 mL, and stirred at 25° C. at a stirring rate of 500 r / min to obtain a mixed solution A.

[0053] (2) A 100 mL aluminum chloride solution with a molar concentration of 1 mol / L is added to the mixed solution A and stirred evenly to obtain a mixed solution B.

[0054] (3) A 5 mol / L NaOH solution was added dropwise to the mixed solution B until the pH of the mixed solution B was between 7.0 and 8.0, thereby obtaining a suspension C.

[0055] (4) The suspension C was allowed to stand for 20 hours, washed three times with water, and then alcoholized three times, and finally centrifuged and freeze-dried for 24 hours to obtain a composite adsorbent 1.

[0056] Example 5

[0057] A method for preparing a composite adsorbent comprises the following steps:

[0058] (1) Chitosan powder with a mass concentration of 5 g / L and a weight of 5 g was added to a citric acid solution with a volume fraction of 2% and a volume of 125 mL, and stirred at 25° C. at a stirring rate of 500 r / min to obtain a mixed solution A.

[0059] (2) A 100 mL aluminum chloride solution with a molar concentration of 3 mol / L was added to the mixed solution A and stirred evenly to obtain a mixed solution B.

[0060] (3) A 5 mol / L NaOH solution was added dropwise to the mixed solution B until the pH of the mixed solution B was between 7.0 and 8.0, thereby obtaining a suspension C.

[0061] (4) The suspension C was allowed to stand for 20 hours, washed three times with water, and then alcoholized three times, and finally centrifuged and freeze-dried for 24 hours to obtain the composite adsorbent 2.

[0062] Example 6

[0063] A method for preparing a composite adsorbent comprises the following steps:

[0064] (1) Chitosan powder with a mass concentration of 5 g / L and a weight of 5 g was added to a citric acid solution with a volume fraction of 2% and a volume of 125 mL, and stirred at 25° C. at a stirring rate of 500 r / min to obtain a mixed solution A.

[0065] (2) A 100 mL aluminum chloride solution with a molar concentration of 5 mol / L is added to the mixed solution A and stirred evenly to obtain a mixed solution B.

[0066] (3) A 5 mol / L NaOH solution was added dropwise to the mixed solution B until the pH of the mixed solution B was between 7.0 and 8.0, thereby obtaining a suspension C.

[0067] (4) The suspension C was allowed to stand for 20 hours, washed three times with water, and then alcoholized three times, and finally centrifuged and freeze-dried for 24 hours to obtain composite adsorbent three.

[0068] Comparative Example 1

[0069] A method for preparing a composite adsorbent comprises the following steps:

[0070] (1) Chitosan powder with a mass concentration of 5 g / L and a weight of 5 g was added to a citric acid solution with a volume fraction of 2% and a volume of 125 mL, and stirred at 25° C. at a stirring rate of 500 r / min to obtain a mixed solution A.

[0071] (2) A 5 mol / L NaOH solution was added dropwise to the mixed solution A until the pH of the mixed solution A was between 7.0 and 8.0, thereby obtaining a suspension C.

[0072] (4) The suspension C was allowed to stand for 20 hours, washed three times with water, and then alcoholized three times, and finally centrifuged and freeze-dried for 24 hours to obtain composite adsorbent 4.

[0073] Comparative Example 2

[0074] A method for preparing a composite adsorbent comprises the following steps:

[0075] (1) A 100 mL aluminum chloride solution with a molar concentration of 5 mol / L was added to a 125 mL citric acid solution with a volume fraction of 2%, and the mixture was stirred at 25° C. at a stirring rate of 500 r / min to obtain a mixed solution A.

[0076] (2) A 5 mol / L NaOH solution was added dropwise to the mixed solution B until the pH of the mixed solution B was between 7.0 and 8.0, thereby obtaining a suspension C.

[0077] (3) The suspension C was allowed to stand for 20 hours, washed three times with water, and then alcoholized three times, and finally centrifuged and freeze-dried for 24 hours to obtain composite adsorbent V.

[0078] Performance Testing

[0079] In order to verify the properties and performance of the composite adsorbent provided in this embodiment, technicians verified the schemes of Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 in subsequent tests and experiments, and tested the adsorption effect of the prepared composite adsorbent on fluoride ions.

[0080] (I) Pore volume and specific surface area of ​​composite adsorbent

[0081] The composite adsorbent prepared in Example 4 was placed in a pore volume and pore size distribution measuring instrument for measurement, and the pore volume of the composite adsorbent prepared in Example 1 was obtained to be 0.38 cm 3 / g, with a specific surface area of ​​230cm 2 / g. And the picture of the composite adsorbent prepared in Example 1 is as follows Figure 1 As shown, by observing Figure 1 Combined with the above data, it can be proved that the composite adsorbent prepared in Example 1 has a porous structure and a higher specific surface area, so it has a stronger adsorption capacity.

[0082] (II) Composition analysis of composite adsorbent

[0083] 2.1 Scanning electron microscopy experiment

[0084] The composite adsorbent prepared in Example 4 was placed under a scanning electron microscope for observation, and the following Figure 2 The data shown. Figure 2 (a) is an electron micrograph of the partial structure of the composite adsorbent in a scanning electron microscope at 100 μm. Figure 2 (b) is an electron micrograph of the partial structure of the composite adsorbent under a scanning electron microscope at 5 μm. Figure 2 (c) is an electron microscope image of the partial structure of the composite adsorbent in the scanning electrode at 10 μm.

[0085] 2.2 EDS spectrum analysis experiment

[0086] The composite adsorbent prepared in Example 4 was put into an EDS spectrometer for analysis, and the obtained Figure 3 .in, Figure 3 The picture on the left is the analysis diagram of the group elements in the composite adsorbent. Figure 3 The picture on the right side shows the distribution of aluminum ions in the composite adsorbent.

[0087] By combining the scanning electron microscopy results and EDS spectrum analysis results of the composite adsorbent prepared in Example 4, it can be seen that: Figure 2 From (a), (b), and (c), it can be seen that the surface of the composite adsorbent prepared in Example 4 has many wrinkles and is distributed with slit-shaped holes or wedge-shaped holes. These structures effectively increase its specific surface area and provide structural support for the high adsorption capacity of the composite adsorbent. Figure 2 (a) and Figure 3 Analysis shows that the surface of the composite adsorbent prepared in Example 4 is uniformly distributed with nano-alumina particles, whose diameter is between 1nm and 10nm, and its inner surface is uneven. The reason for the uneven inner surface may be the result of the complexation of alumina and chitosan.

[0088] 2.3 Transmission electron microscopy experiments

[0089] The composite adsorbent prepared in Example 4 was analyzed under a transmission electron microscope, and the Figure 4 . Figure 4 The middle picture shows the composite adsorbent taken under a transmission electron microscope. Figure 4 The analysis showed that the nanoparticles loaded on the chitosan substrate showed clear lattice fringes, and the measured interplanar spacing was 0.3412 nm. The theoretical value of the (012) crystal plane of the nanoparticles and α-Al2O3 (corundum, trigonal system) (JCPDS 46-1212: ) are highly consistent, and the slight deviation may be caused by the lattice distortion of the nanoparticles or the local stress. The above results directly prove that the alumina in the composite adsorbent exists in the form of a thermally stable α phase. The continuity and regular arrangement of the lattice fringes show that the surface alumina has zero crystallinity, and no obvious lattice defects or distortions are observed. This shows that the loading of chitosan does not significantly destroy the crystal structure of Al2O3, which also explains the preparation and structural stability of the composite adsorbent, providing a reliable crystal phase active site basis for its applications such as adsorption or catalysis.

[0090] 2.4XRD (X-ray diffraction) analysis

[0091] The crystal structure of the composite adsorbent prepared in Example 4 was analyzed by X-ray diffraction technology to obtain Figure 5 . Through Figure 5 Analysis shows that there are broad diffraction peaks at 2θ = 11.2° and 19.8°, with diffuse peaks and low intensity, which are typical characteristics of chitosan amorphous titanium structure. This result shows that the chitosan matrix did not undergo significant crystallization during the composite process, and the disordered arrangement of its molecular chains was retained. Sharp diffraction peaks were detected at 2θ = 31.8°, 45.6°, 56.4°, and 75.4°, and these peaks are highly consistent with the characteristic peaks of crystalline Al2O3 in the standard diffraction data of alumina (JCPDS series cards). For example, the 45.6° peak matches the (400) crystal plane of alumina (JCPDS10-0425). The 75.4° peak corresponds to the high-angle diffraction peak of alumina (such as the (300) crystal plane in JCPDS 46-1212). By comparing with the standard card, it was found that the relative intensity and peak position of the above-mentioned sharp diffraction peaks in all composite adsorbents and the relative intensity and peak position of the characteristic peaks of alumina in the standard card had errors less than ±0.3°, which indicates that the crystalline structure of alumina in the composite adsorbent is complete and there is no significant interference from impurities. This also directly proves that the alumina in the composite adsorbent in Example 4 was successfully loaded onto chitosan, and the loading process did not cause damage to the structure of the chitosan matrix or the alumina particles.

[0092] 2.5 Study on the adsorption mechanism of fluoride ions by composite adsorbent

[0093] In order to further explore the adsorption mechanism of fluoride ions by the composite adsorbent prepared in this example, the present application also compares and analyzes the Fourier transform infrared spectra (FT-IR) of the composite adsorbent prepared in Example 4 before and after adsorbing fluoride ions in photovoltaic wastewater, and obtains Figure 6 . Figure 6 Curve a in the middle is the FT-IR spectrum curve of the composite adsorbent before adsorbing fluoride ions in photovoltaic wastewater. Figure 6Curve b in the middle is the FT-IR spectrum curve of the composite adsorbent after adsorbing fluoride ions in photovoltaic wastewater. Figure 6 Analysis shows that at 3221cm -1 The broad band at 2901cm indicates the presence of -OH and -NH stretching vibrations and is the main absorption peak. -1 The bands at 1582 cm represent the -CH stretching vibrations in -CH and -CH2. -1 The band at 1152cm corresponds to the -NH bending vibration of -NH2. -1 The band at 1061 cm -1 The band at 1000 cm corresponds to the stretching vibration of -CO in -COH. In addition, the FT-IR spectrum also found a band at 1000 cm -1 and 500cm -1 The bands observed between 646cm -1 The Al-O stretching mode was observed.

[0094] Comparing the FT-IR spectra before and after the composite adsorbent, it was found that at 3221 cm -1 and 1582cm -1 The peak intensity is weakened, which is due to the fact that the N atoms in NH and F - A coordination reaction occurs between them to form an N→F coordination bond. -1 The band at also shifted significantly and the peak intensity weakened, which is because -OH participates in the F - The adsorption process. At 1061cm -1 The band at 100° also shifted significantly after adsorption, and the peak intensity increased, which proves that -CO also participates in the adsorption of F. - The increased peak intensity of adsorption may be attributed to the fewer functional groups in the loaded adsorbent. -1 The AL-O stretching band corresponding to the adsorption shifts to 622 cm -1 This indicates that during the adsorption process, the Al-O bond and F - Surface complexation or ion exchange may occur between them.

[0095] In addition, it can be seen from observation that Figure 6 The FT-IR spectra before adsorption (curve a) and after adsorption (curve b) show significant differences in characteristic peak positions and intensities, which reveals the interaction between the functional groups on the surface of the composite adsorbent and the fluoride ions. -1), the broad absorption band at this location after adsorption has a significant red shift and its intensity has weakened, which belongs to the main absorption peak. This change is due to the coordination between the lone pair electron-rich N atoms in the -NH2 group on the surface of the material and F-, forming a stable N→F coordination bond, which leads to a change in the vibration mode of the NH bond. It is worth noting that the NH2 group at 1582cm -1 The -NH bending vibration peak at 1152 cm also showed a shift phenomenon, further confirming the key role of the amino group in the adsorption process. -1 ) attenuation, suggesting that the -OH groups on the surface of the composite adsorbent form OH...F dynamic bonds with F- through hydrogen bonding, and this weak interaction may play an important role in the initial stage of adsorption.

[0096] Of particular note is the -1 The characteristic peak of the -CO group at the site undergoes a significant blue shift and abnormally increases in intensity after adsorption. This phenomenon may be attributed to two mechanisms: on the one hand, F - The introduction of induces the deprotonation process of the carboxylic acid group, resulting in the enhancement of the C=O double bond characteristics; on the other hand, the destruction of the internal hydrogen bond network of the composite adsorbent after adsorption increases the vibration freedom of the -CO group. At the same time, the consumption of some functional groups may trigger the rearrangement of intramolecular charges. The above reasons together lead to the abnormal increase of the absorption peak intensity.

[0097] At 646cm -1 The Al-O stretching vibration corresponding to the adsorption of F on the composite adsorbent - Rear offset to 622cm -1 This indicates that during the adsorption process, the Al-O bond in the composite adsorbent and the F - Surface complexation or ion exchange occurs between them.

[0098] From the above analysis, it can be known that the present invention analyzes the composite adsorbent through FT-IR spectroscopy to reveal the multidimensional adsorption mechanism of the composite adsorbent. The multidimensional adsorption mechanism is as follows: the amino group dominates the chemical adsorption through coordination bonds, the hydroxyl group participates in physical adsorption through hydrogen bonds, and the carboxylic acid group assists ion capture through electrostatic effects to achieve deep fluorine removal. This multi-factor synergistic mechanism not only explains the excellent adsorption performance of the material, but also provides a theoretical basis for the subsequent optimization of material selectivity through functional group modification.

[0099] Combined with the reaction mechanism: amino groups dominate chemical adsorption through coordination bonds, F- forms hydroxyl groups through hydrogen bonds with Al-O bonds to participate in physical adsorption, and carboxylic acid groups assist ion capture through electrostatic effects to achieve deep fluoride removal. It can be summarized that the composite adsorbent prepared by the present invention uses chemical adsorption to form coordination bonds as the main adsorption function, and physical adsorption assists in the adsorption and removal of fluoride ions in photovoltaic wastewater. The reasons can be analyzed from the following content:

[0100] (1) Selective chemical adsorption dominated by coordination bonds

[0101] The lone pair of electrons of the amino group (-NH2) preferentially binds to F - Forming a strong coordination bond (N→F), this specific interaction is due to: F- has a high charge density (small ionic radius, 0.133nm) and strong electronegativity, and can form a stable covalent coordination with the electron cloud of the N atom. 2- (0.230nm) and NO3 - The larger ionic radius of chlorine (0.264 nm) leads to steric hindrance, making it difficult for it to approach the active site of the amino group. Although Cl- (0.181 nm) is similar in size, its polarization ability is weaker (polarizability 3.0×10 - 24 cm 3 vs F - 1.04×10 -24 cm 3 ), so Cl - It is impossible to form an equivalent electron cloud overlap. In summary, the composite adsorbent prepared by the present invention has excellent resistance to interference from the loading matrix and is suitable for effectively adsorbing and removing fluoride ions in high-salinity photovoltaic wastewater.

[0102] (2) Size selectivity of hydrogen bonding

[0103] When hydroxyl (-OH) participates in adsorption through OH···F hydrogen bond: the spherical structure of F- (hydration radius ) can form a multidentate hydrogen bond network. 2- (Hydration radius )'s tetrahedral configuration leads to poor hydrogen bonding adaptability. Cl-(hydration radius ) are similar in size, but their lower charge density (-1 vs -1 of F-) weakens the strength of hydrogen bonds. Therefore, the composite adsorbent prepared by the present invention can specifically bind to fluoride ions even in the presence of many inorganic anions, thereby achieving the purpose of adsorbing and removing fluoride ions.

[0104] (3) Charge density matching of electrostatic interaction

[0105] The carboxylic acid group (-COOH) is deprotonated to form -COO - : F - High charge density (-1 / 0.133nm 3 =5.64e / nm 3 ) and -COO - Produce strong electrostatic attraction. 2-(charge density 2.67e / nm 3 ), Cl - (3.05e / nm 3 ) and NO3 - (2.37e / nm 3 ) has a significantly lower charge density than F - , resulting in a weakening of the Coulomb effect, so the composite adsorbent prepared by the present invention can achieve specific binding to fluoride ions even in the presence of numerous inorganic anions, thereby achieving the purpose of adsorbing and removing fluoride ions.

[0106] (4) Ion exchange specificity of aluminum-oxygen bonds. The ion exchange process of Al-O bonds preferentially replaces F - : F - With OH - With similar ionic radius (F - vs OH - ), which can achieve lattice matching. 2- NO3 - The large size of Cl leads to an increase in the lattice distortion energy barrier. - The size difference leads to an increase in the exchange activation energy (about 25 kJ / mol). Therefore, the composite adsorbent prepared by the present invention can achieve specific binding to fluoride ions even in the presence of a large number of inorganic anions, thereby achieving the purpose of adsorbing and removing fluoride ions.

[0107] (III) Defluorination efficiency of fluoride ions in photovoltaic wastewater

[0108] In order to verify the removal effect of the composite adsorbent prepared by the present invention on fluoride ions in photovoltaic wastewater, the following verification experiment is performed.

[0109] 3.1 Verification of the removal effect of fluoride ions in photovoltaic wastewater by composite adsorbents prepared in different embodiments and comparative examples

[0110] First, the environment of photovoltaic wastewater is simulated in the laboratory: high-grade pure sodium fluoride is prepared to obtain a standard sodium fluoride solution of 10 mg / L, and 3 portions of 1 mg / L standard sodium fluoride solution are taken, each with a volume of 1 L. And the pH of the three standard sodium fluoride solutions are all adjusted to 5.0. Then, the prepared composite adsorbent is used to adsorb and remove fluoride ions in the photovoltaic wastewater: 1 g of composite adsorbent 1 prepared in Example 4 is put into the first standard sodium fluoride solution; 1 g of composite adsorbent 4 prepared in Comparative Example 1 is put into the second standard sodium fluoride solution; 1 g of composite adsorbent 5 prepared in Comparative Example 2 is put into the third standard sodium fluoride solution and stirred for 30 minutes. Measure the residual fluoride ion concentration in the solution: take samples separately and use instruments to determine the concentration of residual fluoride ions in three portions of sodium fluoride solutions to which different composite adsorbents are added. Then, the defluorination efficiency of the three groups of composite adsorbents on the three standard sodium fluoride solutions is obtained by calculation, as shown below: Figure 7 Data shown.

[0111] Through Figure 7 Analysis shows that the defluorination efficiency of the composite adsorbent one prepared in Example 4 for fluoride ions in a standard sodium fluoride solution is 92.3%, the defluorination efficiency of the composite adsorbent four prepared in Comparative Example 1 for fluoride ions in a standard sodium fluoride solution is 35.2%, and the defluorination efficiency of the composite adsorbent five prepared in Comparative Example 2 for fluoride ions in a standard sodium fluoride solution is 43.2%. Among them, the composite adsorbent four prepared in Comparative Example 1 is not added with aluminum chloride solution during the preparation process compared with the composite adsorbent one prepared in Example 4. The composite adsorbent five prepared in Comparative Example 2 is not added with chitosan during the preparation process compared with the composite adsorbent one prepared in Example 4. Judging from the defluorination efficiency of the composite adsorbents prepared in Example 4, Comparative Example 1 and Comparative Example 2 for fluoride ions in photovoltaic wastewater, the defluorination efficiency of the composite adsorbent four prepared in Example 4 for fluoride ions in photovoltaic wastewater is much better than the defluorination efficiency of the composite adsorbents prepared in Comparative Examples 1 and Comparative Examples 2 for photovoltaic wastewater. This proves that the composite adsorbent prepared by loading alumina on chitosan in Example 4 has a good defluorination effect on fluoride ions in photovoltaic wastewater.

[0112] 3.2 Verification of the defluorination effect of the composite adsorbent prepared in this example on fluoride ions in photovoltaic wastewater at different pH values

[0113] First, simulate the photovoltaic wastewater environment: prepare high-grade pure sodium fluoride to obtain a 10 mg / L standard sodium fluoride solution, take 6 portions of 1 mg / L standard sodium fluoride solution, each with a volume of 1 L. Adjust the pH of two portions of the standard sodium fluoride solution to 3.0, the pH of the other two portions of the standard sodium fluoride solution to 5.0, and the pH of the remaining two portions of the standard sodium fluoride solution to 7.0. Then, the prepared composite adsorbent is used to adsorb and remove fluoride ions in photovoltaic wastewater: 1g of the composite adsorbent prepared in Example 4 is put into the first portion of the standard sodium fluoride solution (pH is 3.0); 1g of the composite adsorbent prepared in Comparative Example 2 is put into the second portion of the standard sodium fluoride solution (pH is 3.0). 1g of the composite adsorbent prepared in Example 4 is put into the third portion of the standard sodium fluoride solution (pH is 5.0); 1g of the composite adsorbent prepared in Comparative Example 2 is put into the fourth portion of the standard sodium fluoride solution (pH is 5.0). Put 1g of the composite adsorbent 1 prepared in Example 4 into the fifth portion of a standard sodium fluoride solution (pH 7.0), and put 1g of the composite adsorbent 5 prepared in Comparative Example 2 into the sixth portion of a standard sodium fluoride solution (pH 7.0). Stir the six mixed solutions for 30 minutes respectively. Then take samples respectively and use instruments to measure the concentration of residual fluoride ions in the six sodium fluoride solutions with different pH values. Then calculate the defluorination efficiency of fluoride ions in the six sodium fluoride solutions with different pH values ​​for the six groups of composite adsorbents, and obtain the following: Figure 8 Data shown.

[0114] Through Figure 8 From the data analysis, it can be seen that the defluorination efficiency of the composite adsorbent 1 prepared in Example 4 for fluoride ions in photovoltaic wastewater is higher than 90% in the range of pH 3 to 7, while the adsorption capacity of the composite adsorbent 5 prepared in Comparative Example 2 for fluoride ions in photovoltaic wastewater gradually decreases with the increase of pH. This shows that the composite adsorbent prepared by the preparation method of this embodiment broadens the pH applicable range of the existing composite adsorbent when adsorbing fluoride ions in photovoltaic wastewater, thereby improving the practicality of the composite adsorbent prepared by the preparation method of this embodiment.

[0115] 3.3 Verification of the adsorption effect of the composite adsorbent prepared in this example on fluoride ions under the interference of different anions

[0116] First, prepare high-grade pure sodium fluoride to obtain a 20mg / L sodium fluoride solution. Then select 4 portions of sodium fluoride solutions with a concentration of 20mg / L and a volume of 50mL for use, and adjust the pH of the 4 portions of sodium fluoride solutions to 5.0. Add 50mL of ultrapure water to the first portion of sodium fluoride solution to obtain test solution one. Add 50mL of sodium chloride solution with a concentration of 1mol / L to the second portion of sodium fluoride solution to obtain test solution two. Add 50mL of sodium sulfate solution with a concentration of 1mol / L to the third portion of sodium fluoride solution to obtain test solution three. Add 50mL of sodium nitrate solution with a concentration of 1mol / L to the fourth portion of sodium fluoride solution to obtain test solution four.

[0117] 1 g of the composite adsorbent 1 prepared in Example 4 was added to each of the four groups of test liquids. After stirring for 30 minutes, the four groups of test liquids were sampled and the concentrations of residual fluoride ions in the four groups of test liquids were measured by an instrument. The defluorination efficiency of the composite adsorbent 1 on the four groups of test liquids was calculated, and the results were as follows: Fig. 9 shown.

[0118] Through Fig. 9 The analysis shows that the defluorination efficiency of the composite adsorbent prepared in Example 4 for fluorine ions in the first test liquid is about 92.3%; the defluorination efficiency of the composite adsorbent prepared in Example 4 for fluorine ions in the second test liquid is about 91.5%; the defluorination efficiency of the composite adsorbent prepared in Example 4 for fluorine ions in the third test liquid is about 90.3%; the defluorination efficiency of the composite adsorbent prepared in Example 4 for fluorine ions in the fourth test liquid is about 92.8%. The above data show that in the presence of Cl - 、SO4 2- and NO3 - When these inorganic anions coexist, the composite adsorbent prepared in Example 4 still has a high defluorination efficiency for fluoride ions in photovoltaic wastewater. This proves that the composite adsorbent prepared in this example has excellent resistance to complex matrix interference, and can be used for adsorption and removal of fluoride ions in high-salinity photovoltaic wastewater.

[0119] 3.4 Verification of the defluorination effect of composite adsorbents prepared with different aluminum ion concentrations on fluoride ions in photovoltaic wastewater

[0120] First, the environment of photovoltaic wastewater was simulated in the laboratory: high-grade pure sodium fluoride was prepared to obtain a standard sodium fluoride solution of 10 mg / L, and 3 portions of 1 mg / L standard sodium fluoride solution were taken, each with a volume of 1 L. And the pH of the 3 standard sodium fluoride solutions were all adjusted to 5.0. Then, the fluoride ions in the photovoltaic wastewater were adsorbed and removed by the prepared composite adsorbent: 1 g of composite adsorbent 1 prepared in Example 4 was put into the first standard sodium fluoride solution; 1 g of composite adsorbent 2 prepared in Example 5 was put into the second standard sodium fluoride solution; 1 g of composite adsorbent 3 prepared in Example 6 was put into the third standard sodium fluoride solution and stirred for 30 minutes. Measure the residual fluoride ion concentration in the solution: take samples separately and use instruments to determine the concentration of residual fluoride ions in three portions of sodium fluoride solutions to which different composite adsorbents were added. Then, the defluorination efficiency of the three groups of composite adsorbents for fluoride ions in three standard sodium fluoride solutions was obtained by calculation, as shown below: Fig.10 Data shown.

[0121] Through Fig.10 The data of the analysis show that the defluorination efficiency of fluoride ions in photovoltaic wastewater prepared by the composite adsorbent one in Example 4 is about 92.3%, the defluorination efficiency of fluoride ions in photovoltaic wastewater prepared by the composite adsorbent two in Example 5 is about 94.5%, and the defluorination efficiency of fluoride ions in photovoltaic wastewater prepared by the composite adsorbent three in Example 6 is about 96.8%. It can be seen from the above data that in the preparation process of the composite adsorbent, when the concentration of aluminum ions increases from 1.0 mol / L to 5.0 mol / L, the defluorination efficiency of fluoride ions in photovoltaic wastewater by the composite adsorbent will also increase with the increase of aluminum ion concentration. And in the preparation process of the composite adsorbent, when the concentration of aluminum ions is in the range of 1.0 mol / L to 5.0 mol / L, the defluorination efficiency of fluoride ions in photovoltaic wastewater prepared by the composite adsorbent is greater than 90%, and the concentration of fluoride ions in the photovoltaic wastewater after treatment is measured to obtain the concentration of fluoride ions in the photovoltaic wastewater after defluorination by the composite adsorbent. It is lower than 1.5 mg / L. This indicates that the composite adsorbent prepared in this example has a good defluorination effect on fluoride ions in photovoltaic wastewater.

[0122] The above describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention to be protected. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a composite adsorbent, characterized in that: The -NH2 group, -OH group, -CH2 group and -CO group in the composite adsorbent can specifically bind to the fluoride ions in the photovoltaic wastewater; the preparation method of the composite adsorbent comprises the following steps: 1% to 5% citric acid and 2g / L to 10g / L chitosan are mixed uniformly at a weight ratio of 5:4 to obtain a mixed solution A; Adding an aluminum chloride solution with a molar concentration of 1 mol / L to 5 mol / L into the mixed solution A, and mixing them evenly to obtain a mixed solution B; the volume ratio of the aluminum chloride solution to the mixed solution A is 4:5; Then, an alkali solution is added dropwise to the mixed solution B until the pH of the mixed solution B reaches 7.0-8.0 to obtain a suspension C; The suspension C is allowed to stand for aging, and then washed with water and alcohol for multiple times, and finally centrifugally freeze-dried to obtain the composite adsorbent.

2. The method for preparing the composite adsorbent according to claim 1, characterized in that: The fluorine removal rate of the composite adsorbent in photovoltaic wastewater within the pH range of 3-7 is higher than 90%, and the fluorine ion concentration in the treated photovoltaic wastewater is lower than 1.5 mg / L.

3. The method for preparing the composite adsorbent according to claim 1, characterized in that: The aluminum oxide fixed in the chitosan is amorphous aluminum oxide, and the loading amount of the amorphous aluminum oxide is 15%-35% based on aluminum element.

4. The method for preparing the composite adsorbent according to claim 1, characterized in that: The alkali solution 1 includes one of NaOH, KOH, and NH3·H2O; the molar concentration of the alkali solution 1 is 0.5 mol / L to 10 mol / L.

5. The method for preparing the composite adsorbent according to claim 1, characterized in that: The chitosan has a deacetylation degree of 60%-80% and a molecular weight of 5×10 4 Da~5×10 5 Da; And / or, the static aging time is 10h-20h, and the freeze-drying time is 12h-24h.

6. A composite adsorbent, characterized in that: The composite adsorbent is prepared by the preparation method of the composite adsorbent according to any one of claims 1 to 5. After adsorbing fluoride ions in photovoltaic wastewater, the composite adsorbent can be desorbed and regenerated by alkaline solution 2.

7. The composite adsorbent according to claim 6, characterized in that The alkali solution II includes one of NaOH and KOH; the molar concentration of the alkali solution II is 0.5 mol / L-10 mol / L.

8. The composite adsorbent according to claim 6, characterized in that The composite adsorbent has a porous structure and a pore volume of 0.2 cm 3 / g-0.8cm 3 / g, specific surface area is 100cm 2 / g-800cm 2 / g.

9. Use of the composite adsorbent according to any one of claims 6 to 8, characterized in that: The -NH2 group, -OH group, -CH2 group and -CO group in the composite adsorbent can resist Cl in photovoltaic wastewater. - 、SO4 2- and NO3 - The fluoride ions in photovoltaic wastewater can be removed by chemical adsorption to prevent interference and specifically bind to fluoride ions in photovoltaic wastewater.

10. A method for removing fluoride ions from photovoltaic wastewater, characterized in that: It includes the following steps: Pour the composite adsorbent prepared by the preparation method of the composite adsorbent according to any one of claims 1 to 5 into the photovoltaic wastewater to be treated, and stir; The concentration of fluoride ions in the photovoltaic wastewater is detected in real time by a fluoride ion detection instrument while stirring: if the fluoride ion detection instrument detects that the fluoride ion concentration in the photovoltaic wastewater is higher than 1.5 mg / L, continue to add the composite adsorbent to the photovoltaic wastewater to be treated until the fluoride ion detection instrument detects that the fluoride ion concentration in the photovoltaic wastewater to be treated is lower than 1.5 mg / L.

Citation Information

Patent Citations

  • Modified composite adsorbent as well as preparation method and application thereof

    CN110665469A

  • Mesoporous alumina adsorbent as well as preparation method and application thereof

    CN115779849A

  • Deep fluorine removal agent and application thereof in wastewater of photovoltaic industry

    CN120393971A

  • Chitosan reinforced mixed oxide nanocomposite for fluoride removal from water and a device thereof

    IN201641045048A

  • Novel nanohybrid adsorbent, its synthesis and use for defluoridation of aqueous systems

    IN201721014693A